WormBase 2024: status and transitioning to Alliance infrastructure - Sternberg, Paul W; Van Auken, Kimberly; Wang, Qinghua; Wright, Adam; Yook, Karen; Zarowiecki, Magdalena; Arnaboldi, Valerio; Becerra, Andrés; Brown, Stephanie; Cain, Scott; Chan, Juancarlos; Chen, Wen J; et al. (Genetics (Austin), 2024)
WormBase has been the major repository and knowledgebase of information about the genome and genetics of Caenorhabditis elegans and other nematodes of experimental interest for over 2 decades. We have 3 goals: to keep current with the fast-paced C. elegans research, to provide better integration with other resources, and to be sustainable. Here, we discuss the current state of WormBase as well as progress and plans for moving core WormBase infrastructure to the Alliance of Genome Resources (the Alliance). As an Alliance member, WormBase will continue to interact with the C. elegans community, develop new features as needed, and curate key information from the literature and large-scale projects.